"Are There Any Mexicans Listening?" Stancetaking and Language Ideologies in a Spanish L2 Classroom. Issue 1 (18th April 2022) - Mattson‐Prieto, Raquel; Showstack, Rachel
Abstract: This study investigated classroom interaction through the framework of stancetaking (Du Bois, 2007) to understand how Spanish second language (L2) learners positioned themselves when participating in communicative language learning activities. Data came from transcribed audio and video recordings of three 90‐minute lessons in one intermediate‐level U.S. high school Spanish class. We examined how the students indexed epistemic stances toward their grammar explanations, and affective and evaluative stances toward the Spanish language and native (L1) Spanish speakers during peer interaction. Despite the burgeoning Spanish‐speaking community near where the data were collected, L2 learners' linguistic practices indexed stances of expertise regarding their knowledge of Spanish grammar and vocabulary rather than their potential to meaningfully interact with the people who lived and worked in their community. In addition, some indexed negative affective and evaluative stances toward L1 Spanish speakers. Findings signal the need to examine how target‐language speakers are positioned in classroom practices. Abstract :